The status of Tibet in the diplomacy of China, Britain, the United States and India, 1911-1959 - Askew, Joseph (2002)
This thesis examines the changes in diplomacy of China, the West, Tibet and India from 1911 to 1951, while Tibet functioned as an independent country, and during 1951 to 1959 while under Chinese control. Tibet maintained its own currency, government, armed forces and way of life until 1959. The thesis also examines the cultural shifts in the political, social and military spheres in these countries. It assumes that the general world trend in political life has been towards increasingly intolerant and extreme politics. If Tibet remains part of China with little chance of resuming independence, it is because the Chinese government and people were quicker to adopt radical Western philosophies than the Tibetans were.